Strategi Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Tim Pada Usaha Wirman Sambal - Miftahul Jannah; Andi Indriani Ibrahim; Idris Idris; Suryadi Samudra (Pusat Riset dan Inovasi Nasional, 2024)
The formulation of the problem in this research is whether human resource management strategies play a role in improving team performance, especially in the Wirman Sambal team and what strategies are carried out by Wirman Sambal to improve team performance. Regarding the problems within the Wirman Sambal business group, the author in this research used a qualitative descriptive method. This type of research is a type of research that uses observation, documentation and in-depth interviews as data collection methods. According to Moleong, qualitative research is a number of displays such as spoken or written words that are observed and internalized by the researcher, as well as objects observed that pay attention to every detail to obtain the meaning implicit in the document or object. The data collection technique in this research is by making direct observations in the field. The results of this research show that human resource management strategies greatly influence team performance in the Wirman Sambal business by implementing several human resource management strategies.